Strategies For Implementing The Mudharabah Agreement To Support Sharia-Based Financing For Smes In Cirebon Regency - Mukhammad Gufron; Dini selasi; Imroatul Fatihah (Cirebon International Journal of Economics and Business, 2026)
The mudharabah contract in sharia financing is the primary choice for supporting the development of the Micro, Small, and Medium Enterprises (MSMEs) sector, particularly for those seeking to avoid usury or interest inherent in the conventional banking system. In the mudharabah contract, the investor provides funds managed by the entrepreneur, and profits are shared based on the initial agreement, while losses are borne by the investor, unless the losses result from the negligence of the business manager. This study aims to analyze the implementation of the mudharabah contract in financing MSMEs in Cirebon Regency, assess the existing opportunities and challenges, and provide recommendations for development. Using a qualitative approach, in-depth interviews were conducted with MSME owners who have utilized the mudharabah contract as a source of financing. The results of the study indicate that the mudharabah contract has the potential to encourage the growth of MSMEs in Cirebon Regency, although challenges such as limited understanding, suboptimal management, and a lack of assistance from Islamic financial institutions remain obstacles